INTERNAL QUALITY ASSURANCE SYSTEM DEVELOPMENT: CURRENT STATUS AND SOLUTIONS TO MEET VINH UNIVERSITY’S STRATEGIC DEVELOPMENT OBJECTIVES FOR 2022-2030, VISION TO 2045 - Dinh Thi Nga*, Hoang Phan Hai Yen (Tạp chí Khoa học)
This study assesses the current development and operation of the internal quality assurance (IQA) system at Vinh University within the framework of its strategic development plan for 2022- 2030, with a vision for 2045. Through an analysis of quality management mechanisms, processes, survey data, and expert opinions, the study clarifies the organizational structure, implementation methods, and responsiveness of the IQA system in achieving the university's strategic objectives. Based on these findings, the paper proposes solutions to enhance the effectiveness of the IQA system, thereby ensuring educational quality and improving Vinh University's standing in the national and international higher education landscape.